LOCAL GOVERNMENT UNITS 3: BARANGAY DEVELOPMENT MANAGEMENT SYSTEM FOR ZONING AND PERMIT PROCESSING WITH AI-DRIVEN DECISION SUPPORT TOOLS (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Barangays serve as the foundational administrative units in the Philippines, responsible for public service delivery, regulatory enforcement, and land-use management through zoning and permit processing. However, many barangays continue to rely on manual workflows, which often result in inefficiencies such as misplaced documents, delayed processing times, and a lack of transparency. These issues are exacerbated in rapidly urbanizing areas where demand for zoning and permit approvals is rising. This study presents the Barangay Development Management System (BDMS), a digital platform designed to modernize and streamline these essential processes. The BDMS was developed using the Agile Scrum methodology, enabling iterative development and continuous feedback. Core technologies used include PHP, HTML, CSS, JavaScript, and MySQL, with Visual Studio Code as the main development environment. The system integrates various modules for zoning applications and permit processing, along with a basic AI-driven decision support tool that provides data-informed suggestions to assist barangay officials. Before deployment, user acceptance testing was planned to validate system functionality and usability. The BDMS successfully digitized key administrative functions, enhancing the efficiency of zoning and permit workflows. The system facilitated faster processing of applications, improved document and user record management, and ensured stable performance under multi-user conditions. The inclusion of an AI-driven tool supported more informed decision-making. Barangay officials reported improved service delivery, better internal coordination, and enhanced transparency in local governance operations. The system demonstrated strong potential in addressing the inefficiencies of manual zoning and permit processing within barangay operations. Its responsive administrative dashboard and automated reporting capabilities contributed to more effective decision-making and reduced administrative workload. While the system performed reliably, ongoing refinements are recommended to accommodate increasing data volumes and evolving user needs. The BDMS offers a scalable and practical solution for modernizing barangay governance through digital transformation.
Keywords: barangay management; zoning system; permit processing; ai decision support; digital governance; agile scrum; local government; workflow automation; public service efficiency; urban planning